MY PROFESSIONAL JOURNEY: AN AUTOBIOGRAPHICAL NARRATIVE - Canh, Le Van (VNU Journal of Foreign Studies; Vol 34 No 5DO - 10.25073/2525-2445/vnufs.4294, 2018)
This paper underscores the dynamic and complex dimensions of my being and becoming an applied linguist. It employs autobiography as an approach to my engagement in self-reflexivity on the professional re-construction of myself. The purpose behind this self-reflective account is to encourage an access to localized ways of knowing, being, and becoming in the world. That access is much needed in language education research in the era in which epistemological understandings are in flux. The paper concludes by discussing how I re-construe my own professional experiences.